To evaluate the protective effect of sunscreen in the incidence of melasma among medical students - . Nadia Sultan (Journal of Pakistan Association of Dermatologists, 2022)
Objective The objective is to evaluate the protective effect of sunscreen usage in the occurrence of melasma among medical students. Methods The study was conducted in the outpatient department of Dermatology at Punjab Rangers Teaching Hospital over a period of 6 weeks starting from August 2020 till mid of September 2020. A questionnaire was circulated among the medical students of Rahbar Medical & Dental College regarding the usage of sunscreen & occurrence of melasma. Results Total 169 students responded ,93 (55%) females & 76 (45%) males. 104 (61.5%) students reported using sunscreen, 36 (36.6%) regularly (at least once daily) & 68 (65.3%) occasionally (once or twice a week), while the remaining 65 (38.4%) had never applied sunscreen. Based on sunscreen usage, the students were allocated groups, A & B respectively. Users were further subdivided into Regular users (A1) & Occasional users (A2). The incidence of melasma among 104 students in group A was 37 (35.5%) while the remaining 67 (64.4%) students did not claim any sort of hyperpigmentation on their face. On the other hand, out of 65 (38.4%) students of group B who had never applied sunscreen, 37 (56.9%) reported melasma while the remaining 28 (43%) did not. Conclusion Regular application of sunscreen provides adequate sun protection to yield a shielding effect against photo pigmentation. On the contrary, occasional use does not confer much protection against the occurrence of melasma.